2020
DOI: 10.1080/15140326.2020.1711592
|View full text |Cite
|
Sign up to set email alerts
|

Revisiting the Feldstein-Horioka puzzle for Turkey

Abstract: The domestic saving and investment correlation as posited by Feldstein and Horioka is revisited for Turkey and tested over the whole period and the two subperiods (1950-1989 and 1990-2017). The time-series properties of the data and the presence of structural breaks are properly addressed by the bounds testing procedure. Although, the investment and savings are positively correlated during the period of restricted capital mobility and negatively correlated during the period of perfect capital mobility acco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 29 publications
0
3
0
2
Order By: Relevance
“…But the research outcomes are mixed in explaining this hypothesis. Several studies concluded the existence of a high degree of savingsinvestment association and thus, low level of international capital mobility thereby supporting F-H hypothesis in large and small economies (Akkoyunlu, 2020;Lam, 2012;Bagheri & Hazrati, 2012;Eyuboglu & Uzar, 2020;Hassan et al, 2014;Irandoust, 2019;Petreska & Mojsoska-Blazevski, 2013;Tasar, 2017;Yildirim & Orman, 2018). Nevertheless, this correlation was found to be weaker for developing economies (Adeniyi & Egwaikhide, 2013;Bangaké & Eggoh, 2010;Chan et al, 2011;Chang & Smith, 2014;Coakley et al, 1999;De Wet & Van Eyden, 2005;Dooley et al, 1987;Horioka et al, 2015;Kasuga, 2004;Mamingi, 1997;Mumtaz & Munir, 2016;Patra & Mohanty, 2020;Payne & Kumazawa, 2005;Raheem, 2017;Shahbaz et al, 2010;Sinha & Sinha, 2004;Vamvakidis & Waczairg, 1998;Wong, 1990;Younas, 2007).…”
Section: Literature Reviewmentioning
confidence: 91%
See 2 more Smart Citations
“…But the research outcomes are mixed in explaining this hypothesis. Several studies concluded the existence of a high degree of savingsinvestment association and thus, low level of international capital mobility thereby supporting F-H hypothesis in large and small economies (Akkoyunlu, 2020;Lam, 2012;Bagheri & Hazrati, 2012;Eyuboglu & Uzar, 2020;Hassan et al, 2014;Irandoust, 2019;Petreska & Mojsoska-Blazevski, 2013;Tasar, 2017;Yildirim & Orman, 2018). Nevertheless, this correlation was found to be weaker for developing economies (Adeniyi & Egwaikhide, 2013;Bangaké & Eggoh, 2010;Chan et al, 2011;Chang & Smith, 2014;Coakley et al, 1999;De Wet & Van Eyden, 2005;Dooley et al, 1987;Horioka et al, 2015;Kasuga, 2004;Mamingi, 1997;Mumtaz & Munir, 2016;Patra & Mohanty, 2020;Payne & Kumazawa, 2005;Raheem, 2017;Shahbaz et al, 2010;Sinha & Sinha, 2004;Vamvakidis & Waczairg, 1998;Wong, 1990;Younas, 2007).…”
Section: Literature Reviewmentioning
confidence: 91%
“…Following the empirical conventions for studying F–H puzzle (Akkoyunlu, 2020), we have taken Gross domestic savings as a percentage of GDP and Gross fixed capital formation as a percentage of GDP as measures of domestic savings and domestic investments, respectively. The annual data for these two variables for the sample period have been compiled from the world development indicators database of the World Bank.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Ayrıca, bazı yeni çalışmalarda, içsel olarak belirlenmiş yapısal kırılma modelleri kullanılarak FHB'nin geçerliliğini araştırmıştır. Akkoyunlu (2020Akkoyunlu ( ), 1950Akkoyunlu ( -2017Akkoyunlu ( , 1950Akkoyunlu ( -89 ve 1990Akkoyunlu ( -2016 dönemleri için FHB'nin Türkiye'deki geçerliliğini araştırmış ve 1950 -2017 dönemi için sınırlı sermaye hareketliliği ve negatif tasarruf ile pozitif bir tasarruf-yatırım korelasyonu ve 1990 -2017 dönemi için ise yüksek sermaye hareketliliği ile yatırım korelasyonu saptamıştır. Diğer yandan Patra ve Mohanty (2020) ise, 1960 -2017 yılları arasındaki dönem için 6 büyük Güney Asya ülkesinde FHB'nin geçerliliğini Markov-anahtarlama regresyonu kullanarak araştırmış ve FHB'nin rejim değişikliklerine bağlı olarak bazı dönemler için geçerli olduğunu saptamıştır.…”
Section: (I / Y)i = α + β (S / Y)i + μIunclassified
“…Tam sermaye hareketliliği yoksa yatırım tasarruf korelasyonunun değeri bire yakın çıkmaktadır (Obstfeld ve Rogoff, 2000: 349). Feldstein ve Horioka (1980), 1960-1974 Akkoyunlu (2018Akkoyunlu ( ), 1950Akkoyunlu ( -2017Akkoyunlu ( (1950Akkoyunlu ( -1989Akkoyunlu ( ve 1990Akkoyunlu ( -2017 Veri ve Metodoloji Çalışmada, Türkiye'de tasarruf ve yatırım arasındaki ilişkinin incelenmesi amacıyla, ele alınan döneme ait yıllık veriler ile Feldstein-Horioka hipotezinin geçerliliği test edilmiştir. Ampirik olarak yapılan araştırmada kullanılan değişkenlere ilişkin bilgiler aşağıdaki Tablo 1'de gösterilmiştir.…”
Section: Kuramsal Temel Ve Literatürden öRneklerunclassified